Elevated levels of FN1 and CCL2 in bronchoalveolar lavage fluid from sarcoidosis patients. Issue 1 (December 2016) - Hamsten, Carl; Wiklundh, Emil; Grönlund, Hans; Schwenk, Jochen; Uhlén, Mathias; Eklund, Anders; Nilsson, Peter; Grunewald, Johan; Häggmark-Månberg, Anna
Abstract Background Sarcoidosis is a granulomatous systemic inflammatory disease in which more than 90 % of all patients develop pulmonary manifestations. Several gene associations have previously been described, but established and clinically useful biomarkers are still absent. This study aimed to find proteins in bronchoalveolar lavage (BAL) fluid that can be associated with the disease. Methods We developed and performed profiling of 94 selected proteins in BAL fluid and serum samples obtained from newly diagnosed and non-treated patients with sarcoidosis. Using multiplexed immunoassays, a total of 317 BAL and 217 serum samples were analyzed, including asthmatic patients and healthy individuals as controls. Results Our analyses revealed increased levels of eight proteins in sarcoidosis patients compared to controls. Out of these, fibronectin (FN1) and C-C motif chemokine 2 (CCL2) revealed the strongest associations. In addition, cadherin 5 (CDH5) was found to correlate positively with lymphocyte cell numbers in BAL fluid. Conclusions Applying a high throughput proteomics screening technique, we found proteins of potential clinical relevance in the context of sarcoidosis.